Back to Basics Part 1: Are We Over Treating Ocular Hypertension and Primary Open Angle Glaucoma Patients? - S. A. Raja, S. Aqil, Rashid Zia (Pakistan Journal of Ophthalmology, 2019)
Population explosion, availability of life saving drugs and perusal of healthier life styles is leading to rising life expectancy worldwide. This indirectly translates to increasing prevalence of open angle glaucoma1 worldwide and Pakistan is no exception to these myriad factors of population increase and related healthcare issues. Studies have in general shown increased glaucoma severity corelating with direct and indirect costs associated with the progression of disease2. Hence there is a wide spread tendency to treat suspicious optic nerve heads, mild to moderate high intraocular pressures or even documented but non progressive glaucoma damage without comprehensive structural, visual function, local and systemic risk assessment. This has in turn led to plethora of adverse clinical, socioeconomic and financial concerns triggering chain of adversities at individual and as well as national level.